Hardware Implementation of Fast Recursive Walsh-Hadamard Transform - Mazumder, Pulak; Middya, Rajarshi; Naskar, Mrinal Kanti (International Journal of Computer Sciences and Engineering, 2025)
The Walsh Hadamard Transform is an extremely relevant concept in modern digital image data compression. This paper examines the feasibility of using a tensor product based approach to Walsh Hadamard Transfrom for implementation to hardware architecture using FPGA technology. This paper explains the derivation of a highly parallel and very fast algorithm for the computation of both one-dimensional and two-dimensional transforms using tensor product. Such a fast dedicated hardware design for the Walsh Hadamard Transform will help a wide range of digital signal processing applications.